Illocutionary Acts in Spider-Man: No Way Home - Sudiyono, Boyke Adimas Triyogo; Komang Dian Puspita Candra; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Illocutionary act refers to an act of doing something. This study was focused on the types of illocutionary act that found in the movie entitled Spider-Man: No Way Home. This study applied descriptive qualitative method in conducting the research. The library research was also used to collect the research data. In analyzing the data, the theory that proposed by Searle (1976) was applied in identifying the types of illocutionary act in the movie. Based on the results of this study, there were 100 data of illocutionary act that can be divided into 34 (34%) data of assertive act, 18 (18%) data of directive act, 24 (24%) data of commissive act, 22 (22%) data of expressive act, and 2 (2%) data of declarative act. The most dominant illocutionary act that occurred in this movie was assertive act.